2020
DOI: 10.1016/j.compstruct.2020.112300
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compressive behavior of a novel ultra-lightweight cement composite incorporated with rubber powder

Abstract: This paper develops a novel rubberized ultra-lightweight high ductility cement composite (RULCC) with added rubber powder and low content PE fiber (0.7%), and investigates the dynamic compressive response and failure mechanism of the RULCC both experimentally and analytically. The test program examines the dynamic compressive stress-strain relationship of the RULCC through Split Hopkinson Pressure Bar (SHPB) impact tests. The results show that the rubber powder aggregates have significant effect on the compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 32 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…The novel rubberized ultra-lightweight high ductility cement composite (RULCC) to be modelled is composed of cement, fly ash cenospheres (FAC), silica fume, rubber powder aggregates and polymer polyethylene (PE) fibers. The RULCC has a target 28-day compressive strength around 35MPa with a low density of around 1450kg/m Further details about the manufacturing process of the materials can be found in Huang et al [46].…”
Section: Experimental Data For Model Validation 21 the Rubberized Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The novel rubberized ultra-lightweight high ductility cement composite (RULCC) to be modelled is composed of cement, fly ash cenospheres (FAC), silica fume, rubber powder aggregates and polymer polyethylene (PE) fibers. The RULCC has a target 28-day compressive strength around 35MPa with a low density of around 1450kg/m Further details about the manufacturing process of the materials can be found in Huang et al [46].…”
Section: Experimental Data For Model Validation 21 the Rubberized Materialsmentioning
confidence: 99%
“…To evaluate the properties of the material, the mixes with seven different rubber and fiber contents were tested in Huang et al [46], as listed in Table 1, which includes the replacement ratios of rubber contents (5%, 10%, 15% and 20%) and fiber contents (0% and 0.7%). The mechanical properties of the PE fibers are shown in Table 2.…”
Section: Experimental Data For Model Validation 21 the Rubberized Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of earlier experiments [18][19][20][21][22][23][24] also suggested that it was possible to effectively improve cementation between rubber powders and cement and increase the flexural and compressive strength of rubber cement-based composite materials by giving specific treatments to the surface of rubber powders. For example, Senouci et al removed the stains on the surface of rubber powders simply by soaking and rinsing; Rostami et al soaked and cleaned the rubber powders with distilled water, CCl 4 reagent, and organic mixed emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the continuous development of new raw materials has enriched the materials in the field of construction [ 1 , 2 , 3 , 4 ], among which the treatment and recovery of solid waste are of great significance for environmental protection, such as the utilization of recycled tyre polymer fiber as concrete reinforced materials by Chen et al [ 1 ], the incorporation of construction and demolition wastes as recycled aggregates by Rodríguez et al [ 2 ], and the utilization of waste tyre rubber as concrete material by Huang et al [ 3 ] and Gupta et al [ 4 ]. The scrap tyre has become one of the most problematic solid wastes throughout the world, and many researchers have proved that scrap tyres are sources of valuable raw materials [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%